Pengetahuan Literasi Jasmani Pada Siswa Kelas X SMAN Kalisat - Guruh Permadi Yoga Saputra; Riski Apriliyanto; Bahtiar Hari Hardovi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to provide a comprehensive picture of the physical literacy knowledge of class X students at SMAN Kalisat Jember. Measurement of physical literacy understanding using 9 items of the